Выбор допускаемых напряжений в условиях абразивного изнашивания - Приймаков, А. Г.; Устиненко, Александр Витальевич (НТУ "ХПИ", 2006)
The criteria estimation of comparative endurance of materials is given in view of structural adaptation to conditions of a working environment. The level of an anisotropy and complexity of a structural condition of surfaces of abrasive chafing, with the help of the Fourier-assaying is quantitatively estimated. It is shown how to realize a choice of supposed stress at presence of an abrasive in a friction zone
Keywords: изнашивание поверхности; контактирующие тела; Фурье-анализ; коэффициент достигнутой анизотропии